2013
DOI: 10.1080/02640414.2013.778419
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure of practice activities engaged in by elite and recreational youth cricket players

Abstract: Practice plays an important role in skill acquisition, although not all practice is of equal quality. We examined the types of team practice activities in four groups of youth cricket players. The groups were recreational- and elite-children (9 to 12 years of age) and recreational- and elite-adolescent players (13 to 17 years of age). Time motion analysis recorded the duration in two types of practice activities, namely, Training Form and Playing Form. Training Form is mainly drill-type activities, whereas Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…For applied coaching research to prove wholly worthwhile, a crucial aspect to consider is its impact within representative settings. Unfortunately, recent attempts to evaluate coaching practice have suggested a consistent discrepancy between current recommendations from the skill acquisition and performance literature and knowledge-bases and/or behaviours of coaches (Cushion, Ford & Williams, 2012;Low, Williams, McRobert & Ford, 2013;Millar, Oldham & Donovan, 2011;Porter, Wu & Partridge, 2010). A notable limitation of these studies, however, has been coaches' assumed intended training outcomes.…”
Section: The Research-practice Gap: What Evidence Suggestsmentioning
confidence: 99%
“…For applied coaching research to prove wholly worthwhile, a crucial aspect to consider is its impact within representative settings. Unfortunately, recent attempts to evaluate coaching practice have suggested a consistent discrepancy between current recommendations from the skill acquisition and performance literature and knowledge-bases and/or behaviours of coaches (Cushion, Ford & Williams, 2012;Low, Williams, McRobert & Ford, 2013;Millar, Oldham & Donovan, 2011;Porter, Wu & Partridge, 2010). A notable limitation of these studies, however, has been coaches' assumed intended training outcomes.…”
Section: The Research-practice Gap: What Evidence Suggestsmentioning
confidence: 99%
“…Ford et al (2010) found that youth soccer coaches used an average of 65% drill-like training form activities and 35% game-like playing form activities. Similarly, Partington and Cushion (2013) (53% training form; 47% playing form) in male professional youth soccer, and Low et al (2013) (69% training form; 19% playing form) in male youth cricket, found that the greatest proportion of training time was spent in less game-like activities. Finally, Harvey and colleagues' (2013) study of three collegiate field hockey (41% training form; 35% playing form), basketball (41% training form; 36% playing form) and volleyball (45% training form; 39% playing form) coaches also reported a preference for training form activities.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the Game Sense coaching philosophy, which is espoused by researchers (e.g., Evans & Light, 2007;Light & Evans, 2010;Thomas & Wilson, 2014) and promoted by several governing bodies of rugby union (Harvey & Jarrett, 2014;Light, 2013;Reid, 2003). The Game Sense approach places practical emphasis on developing training activities that reflect the demands of actual matches, providing opportunities for players to develop the skills (perceptual, cognitive and motor) relevant to successful competitive performance (Low et al, 2013). Moreover, gamecentred approaches have been heralded as the contexts in which coach behaviours that support long-term learning will be more likely to occur (Partington & Cushion, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The training activities used by cricket coaches can typically be classified by training form and playing form. 42 Firstly, training form is defined as those activities practised in isolation or in small groups lacking competitive aspects, such as net-based batting and bowling as well as fielding drills. 42 Information regarding the physical demands of fast bowlers during training form activities such as net-based bowling is surprisingly limited despite this being the most common method for cricket training.…”
Section: Physical Demands Of Fast Bowlers During Training and Simulatmentioning
confidence: 99%